TESTING OPTICALLY STIMULATED LUMINESCENCE DATING OF SAND-SIZED QUARTZ AND FELDSPAR FROM FLUVIAL DEPOSITS - Wallinga J.; Murray A.S.; Duller G.A.T.; Tornqvist T.E. (My University, 2001)
We apply single-aliquot optically stimulated luminescence (OSL) dating to quartz- and feldspar-rich extracts from fluvial channel deposits of the Rhine-Meuse system in The Netherlands. The time of deposition of these deposits is tightly constrained by radiocarbon dating or historical sources. This allows us to compare OSL ages obtained on quartz and infrared OSL (IR-OSL) ages obtained on potassium-rich feldspar with independent ages over the range of 0.3-13 ka. We show that the quartz OSL ages are in good agreement with the expected age. Using IR-OSL dating of feldspar, we find a slight age overestimate for the youngest sample, whereas for older samples the age is significantly underestimated. We also apply OSL dating to older fluvial and estuarine channel deposits with limited independent chronological constraints. Comparison of feldspar IR-OSL ages with the quartz OSL ages up to ~200 ka shows a clear trend, where the former severely underestimates the latter. This trend is similar to that found for the samples with independent age control, indicating that the feldspar IR-OSL ages are erroneously young for the entire age range. In the youngest samples, incomplete resetting of the IR-OSL signal prior to deposition probably masks the age underestimation. We show that the IR-OSL age underestimation is partly caused by changes in trapping probability due to preheating. Correction for this phenomenon improves the IR-OSL ages slightly, but does not provide a complete solution to the discrepancy. We suggest that, in the light of the problems encountered in the IR-OSL dating of feldspar, quartz is the mineral of choice for OSL dating of these deposits. However, feldspar dating should continue to be investigated, because it has potential application to longer time scales.
Keywords: OPTICALLY STIMULATED LUMINESCENCE DATING; QUARTZ; FELDSPAR GROUP; STREAM SEDIMENTS; AGE